2015
DOI: 10.1186/s12909-015-0428-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment at UK medical schools varies substantially in volume, type and intensity and correlates with postgraduate attainment

Abstract: BackgroundIn the United Kingdom (UK), medical schools are free to develop local systems and policies that govern student assessment and progression. Successful completion of an undergraduate medical degree results in the automatic award of a provisional licence to practice medicine by the General Medical Council (GMC). Such a licensing process relies heavily on the assumption that individual schools develop similarly rigorous assessment policies. Little work has evaluated variability of undergraduate medical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 21 publications
1
35
1
1
Order By: Relevance
“… 7–10 This finding might also suggest that there is value in increasing assessment frequency at medical schools to drive learning. 11 Surprisingly, question writing frequency also increased around examinations. This suggests a proportion of students found writing questions a worthwhile revision technique, despite the time commitment:…”
Section: Discussionmentioning
confidence: 97%
“… 7–10 This finding might also suggest that there is value in increasing assessment frequency at medical schools to drive learning. 11 Surprisingly, question writing frequency also increased around examinations. This suggests a proportion of students found writing questions a worthwhile revision technique, despite the time commitment:…”
Section: Discussionmentioning
confidence: 97%
“…Schools differ not only in how they teach but in how they assess [23] and the standards that are set [8], the GMC report commenting that "There is also the moot point about how students are assessed. There is some evidence that assessment methods and standards for passing exams vary across medical schools."…”
Section: Problem-based Learning Schoolsmentioning
confidence: 99%
“…Studies have shown medical school education has an impact on postgraduate performance. Medical students with more intense undergraduate assessments went on to do better in postgraduate membership examinations such as MRCP and MRCGP (Devine et al 2015). This suggests that the style of undergraduate training may be a better determinant of academic ability than the current educational performance ranking system, highlighting the potential need for a standardised examination to clearly identify the more academically able students.…”
Section: Dear Sirmentioning
confidence: 99%